The Implementation Of School Operational Assistance Program Policy In The Basic Education In Wajo Regency - Aminah, Sitti; Ismail, Imran; Fatahangi, Andi (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
The government has endeavoured to realize the goals of educating the children through the National Education System. However, in some situations, the implementation of this effort has fallen short of expectations because certain practices—like managing school operational cost assistance funds—show less than ideal support in meeting educational standards. This research aims to describe and analyse the implementation of the School Operational Assistance Program (SOA) policy in Wajo Regency, South Sulawesi Province, Indonesia. The research method used is qualitative descriptive research and the data is analyzed using a policy theory approach with three dimensions: organization, interpretation and application. The research results show that the implementation of the policy for managing school operational costs in basic education in the Wajo area has been carried out by technical instructions which have been explained through organizational, interpretation and application aspects as well as through socialization, coordination and reference to the Ministry of Education and Culture database. The supporting factor for implementing this policy is the availability of resources as a means of supporting learning services to students where communication between implementers is established smoothly and program implementers are properly responsible for following their respective duties.